Pengembangan Website Rumah Sakit Islam Ar-Rasyid Palembang Sebagai Sarana Informasi dan Promosi Digital - Heriyanto, Heriyanto; Wijaya, Novan (MDP Student Conference, 2025)
A hospital is a healthcare institution that plays a role in providing information to the public. In today's digital era, the need for information media continues to increase. One of these is the company website, which serves as an information medium connecting hospitals with the community. The purpose of this research is to develop a website for Ar-Rasyid Islamic Hospital Palembang, with development carried out using the RUP (Rational Unified Process) method which includes the Inception, Elaboration, Construction, and Transition phases. The website is developed with a focus on features such as profile pages, service information, news, and doctor schedules. The result of this research is that with the presence of the hospital website, it is expected to improve the services of Ar-Rasyid Islamic Hospital Palembang and extend their information reach to the community without having to visit the hospital directly.